THE IMPACT OF LACTATION EDUCATION AND FAMILY SUPPORT ON BREASTFEEDING CONFIDENCE IN THIRD TRIMESTER FIRST-TIME MOTHERS AT TARUS HEALTH CENTER, KUPANG - Fajriah, Asruria Sani; Mase, Flora A.; Putri, Santy Irene (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
Background: Breastfeeding is essential for providing newborns with necessary nutrients crucial for growth and development. Lactation management involves preparing mothers and families to support successful breastfeeding. Self-efficacy, or a mother's confidence in her ability to breastfeed, influences her decision to breastfeed and her response to challenges.Method: This study employed a one-group pretest-posttest design, focusing on third-trimester primigravida mothers in the Tarus Community Health Center working area, Kupang Regency, with a population of 67. Using purposive sampling, the study evaluated the impact of education on lactation management and family support on breastfeeding self-efficacy.Result: The Wilcoxon test results showed a significant improvement in self-efficacy after the intervention (Asym.Sig = 0.000, p < 0.05).Conclusion: These findings suggest that providing education on lactation management and family support can significantly enhance breastfeeding self-efficacy in expectant mothers, thereby promoting successful breastfeeding practices.